Analisis Penerapan Akad Murabahah Di Bank Syariah Indonesia (BSI) KCP Medan Sukaramai - Mhd. Aziz Alfarisi Hasibuan (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The implementation of the Murabahah agreement at Bank Syariah Indonesia (BSI) KCP Medan Sukaramai is the focus of this research. The aim of the research is to analyze the process of implementing the Murabahah contract, identify the obstacles faced, and initiate efforts to overcome these obstacles. The research method used is a qualitative descriptive method with data collection techniques through in-depth interviews. Respondents consisted of bank managers, bank employees and customers involved in transactions using Murabahah contracts. Data analysis was carried out taking into account relevant sharia principles. The research results show that the implementation of the Murabahah contract at BSI KCP Medan Sukaramai has been carried out carefully and structured in accordance with sharia principles. However, the obstacles faced include a lack of customer understanding of sharia principles as well as differences in understanding between customers and bank officers. Efforts made by banks to overcome these obstacles include increasing education for customers and regular training for bank officers. This research contributes to the understanding of Murabahah contract practices in the sharia banking sector, as well as offering recommendations for banks to increase the effectiveness and efficiency of implementing Murabahah contracts. In addition, it is hoped that this research can provide customers with a better understanding of sharia principles in financial transactions.